Isolation of Phosphate Solubilizing Bacteria Around Bamboo (Bambusa vulgaris) Clumps Using Natural Media Trap Method - Parisya Velayati Furqon; Bambang Fajar Suryadi; Ernin Hidayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Bamboo plant is a potential source of plant growth promoting bacteria (PGPB). Phosphate solubilizing ability is an important characteristic of PGPB. This study aims to isolate phosphate solubilizing bacteria around the bamboo clumps using natural media. The bacteria around the bamboo clumps are trapped using natural media. The media consist of 70 gram cooked rice and 70 gram banana peel. The media were stored in plastic boxes with four types of treatments: 1) tightly closed, 2) covered with tissue, 3) covered with banana leaves, and 4) uncovered (open). Those plastic boxes are placed around the bamboo clump and left for up to 5 days. The trapped phosphate solubilizing bacteria were isolated using Pikovskaya agar. A total of 17 isolates of phosphate solubilizing bacteria were successfully trapped, 8 isolates in cooked rice and 9 isolates in banana peel. The isolates showed a phosphate solubilization index, ranging from 0,2 to 1,40. The isolate NN01 has the highest ability to solubilize phosphate. This isolate was trapped in a cooked rice with an open plastic box condition. NN01 is a Gram positive rod-shaped bacterium. In this study it was revealed that the area of ​​the bamboo clumps is inhabited by various types of bacteria. The natural media of cooked rice and banana peels have a good ability to trap potential phosphate solubilizing bacteria around the bamboo clumps.